Arabidopsis DE-ETIOLATED1 Represses Photomorphogenesis by Positively Regulating Phytochrome-Interacting Factors in the Dark . Issue 9 (23rd September 2014) - Dong, Jie; Tang, Dafang; Gao, Zhaoxu; Yu, Renbo; Li, Kunlun; He, Hang; Terzaghi, William; Deng, Xing Wang; Chen, Haodong
Abstract : Light is a critically important environmental signal regulating plant development, and several repressors have been identified that can inhibit plant photomorphogenesis in the dark. This study reveals a possible mechanism by which two groups of repressors, COP/DET/FUS and PIFs, work in concert to repress photomorphogenesis in darkness. Abstract: Arabidopsis thaliana seedlings undergo photomorphogenic development even in darkness when the function of DE-ETIOLATED1 (DET1), a repressor of photomorphogenesis, is disrupted. However, the mechanism by which DET1 represses photomorphogenesis remains unclear. Our results indicate that DET1 directly interacts with a group of transcription factors known as the phytochrome-interacting factors (PIFs). Furthermore, our results suggest that DET1 positively regulates PIF protein levels primarily by stabilizing PIF proteins in the dark. Genetic analysis showed that each pif single mutant could enhance the det1-1 phenotype, and ectopic expression of each PIF in det1-1 partially suppressed the det1-1 phenotype, based on hypocotyl elongation and cotyledon opening angles observed in darkness. Genomic analysis also revealed that DET1 may modulate the expression of light-regulated genes to mediate photomorphogenesis partially through PIFs. The observed interaction and regulation between DET1 and PIFs not only reveal how DET1 represses photomorphogenesis, but also suggest a possible mechanism by which two groups of photomorphogenic repressors, CONSTITUTIVE PHOTOMORPHOGENESIS/DET/FUSCA and PIFs, work in concert to repress photomorphogenesis in darkness.